The Association Between Sleep Quality and Working Memory of Medical Faculty Malikussaleh University Students - Amri Afra Adilla; Cut Khairunnisa; Cut Sidrah Nadira; Rizka Sofia (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
Background: Working memory is a form of storage of information that is relevant to the activity being worked out in a short time and a limited amount of information. The working memory capacity is influenced by sleep quality. Increased human activity in the modern era, causing less attention to the quality and quantity of sleep. Recent study showed that the prevalence of medical student who have poor sleep quality is quite high, reaching 76%. Poor quality of sleep will cause a person to think and work more slowly, make mistakes, and have a hard time remembering things. Objective: This research aims to know the relationship of sleep quality with working memory capacity in medical students of Malikussaleh University. Methods: This research was an analytical study with cross- sectional approach, and the Fisher test was used as the statistical test. Proportional stratified random sampling was used to  obtained  71 samples of students who had qualified inclusion and exclusion criterias. Results: The results showed that 84,5% of students had poor quality of sleep and 56,3% of students had low working memory capacity. Statistical analysis by Fisher test showed the value of p < 0,05. Conclusion:  there is an association between sleep quality and the capacity of working memory in the Faculty of Medicine students of Malikussaleh University.